Assessment of diet quality and its association with nutritional status among fishermen’s children in Terengganu - Chua, Hwee Shan; Asma’ Ali,; Noor Salihah Zakaria,; Hayati Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this study was to assess diet quality and its association with nutritional status among 7 to 12 years old fishermen’s children in Terengganu. The dietary intake data and nutritional status of 100 fishermen’s children were obtained using twoday 24 hours dietary recall and Body Mass Index. Diet quality of the subjects was assessed using the Healthy Eating Index. 61% of subjects had normal BMI, 22% had a BMI below the normal range, and 17% had their BMI above the normal range. The diet quality of subjects was poor, with mean total HEI score of 50.45±5.27 out of 100 points. The low median scores of the five food groups, particularly for the vegetable (0.83), fruit (0.00) and dairy (0.00) components, indicates the poor compliance of the fishermen’s children with the dietary guidelines. No significant association was found between total HEI score and BMI of the subjects (χ2=0.051, p=0.821). Thus, BMI did not reflect the diet quality of the fishermen’s children in this study. The findings of this study provide additional information on the diet quality and nutritional status of fishermen’s children in Terengganu, on the East Coast of Peninsular Malaysia.